Upaya Kepala Sekolah dalam Membina Profesionalisme Guru di Madrasah Aliyah Fathul Ulum Tebing Tinggi - Jamilah Septiani; A. Khalik; Khairunnas Khairunnas (JMiE (Journal of Management in Education), 2020)
This research aims to describe the efforts of the principal in fostering the professionalism of teachers in Madrasah Aliyah Fathul Ulum Tebing Tinggi. This study uses qualitative methods. Data collection techniques using observations, interviews, and documentation. The results showed that the coaching of teacher professionalism in Madrasah Aliyah Fathul Ulum was carried out through several activities, namely holding teacher coaching once a week; include teachers in workshops and seminars; hold apples every morning for all teachers; and coaching through supervision. The head of madrasah always tries to provide motivation and reward to teachers to continuously improve their skills and become professional teachers in work, especially in providing knowledge to students.